Three-year results of phase I retinal gene therapy trial for CNGA3-mutated achromatopsia: results of a non randomised controlled trial. Issue 11 (18th May 2021) - Reichel, Felix Friedrich; Michalakis, Stylianos; Wilhelm, Barbara; Zobor, Ditta; Muehlfriedel, Regine; Kohl, Susanne; Weisschuh, Nicole; Sothilingam, Vithiyanjali; Kuehlewein, Laura; Kahle, Nadine; Seitz, Immanuel; Paquet-Durand, Francois; et al.
Abstract : Aims: To determine long-term safety and efficacy outcomes of a subretinal gene therapy for CNGA3-associated achromatopsia. We present data from an open-label, nonrandomised controlled trial (NCT02610582 ). Methods: Details of the study design have been previously described. Briefly, nine patients were treated in three escalating dose groups with subretinal AAV8.CNGA3 gene therapy between November 2015 and October 2016. After the first year, patients were seen on a yearly basis. Safety assessment constituted the primary endpoint. On a secondary level, multiple functional tests were carried out to determine efficacy of the therapy. Results: No adverse or serious adverse events deemed related to the study drug occurred after year 1. Safety of the therapy, as the primary endpoint of this trial, can, therefore, be confirmed. The functional benefits that were noted in the treated eye at year 1 were persistent throughout the following visits at years 2 and 3. While functional improvement in the treated eye reached statistical significance for some secondary endpoints, for most endpoints, this was not the case when the treated eye was compared with the untreated fellow eye. Conclusion: The results demonstrate a very good safety profile of the therapy even at the highest dose administered. The small sample size limits the statistical power of efficacy analyses. However, trial results inform on the most promising design and endpoints for future clinical trials. Such trials have to determine whether treatment of younger patients results in greater functional gains by avoiding amblyopia as a potential limiting factor.